Drive, instinct, reflex—Applications to treatment of anxiety, depressive and addictive disorders - Johnson, Brian; Brand, David; Zimmerman, Edward; Kirsch, Michael (Frontiers in Psychology, 2022)
The neuropsychoanalytic approach solves important aspects of how to use our understanding of the brain to treat patients. We describe the neurobiology underlying motivation for healthy behaviors and psychopathology. Motivational concepts can be used guide clinical work. We have updated Freud’s original concepts of drive and instinct using neuropsychoanalysis in a way that conserves his insights while adding information that is of use in clinical treatment. Drive (Trieb) is a pressure to act on an internal stimulus. It has a motivational energic source, an aim, an object, and is terminated by the satisfaction of a surge of serotonin. An instinct (Instinkt) is an inherited pattern of behavior that varies little from species to species. Drives are created by internal/ventral brain factors. Instincts require input from the outside that arrive through dorsal brain structures. In our model unpleasure is the experience of unsatisfied drives while pleasure if fueled by a propitious human environment. These concepts can be used to inform our understanding of, “internal conflict”, and solve problems involving treatment of anxiety and depression, autism, fibromyalgia, addiction in general and specific problems of opioid use disorder. Our description of motivation in addictive illness shows that the term, “reward system,” is incorrect, eliminating a source of stigmatizing addiction by suggesting that it is hedonistic.